Feasibility Study Of An Application Of A Saturated Magnetic Core As A Fault Current Limiter - Binduhewa, P.J.; Kumara, J.R.S.S.; Atputharajah, A.; Ekanayake, J.B. (My University, 2005)
The connection of new generators and abnormal operations of the power system increase the fault current over the rating of the electrical equipment in distribution and transmission networks. Different types of Fault Current Limiters (FCL) can be used to limit the fault current. This paper presents a feasibility study of an application of a saturated magnetic core as a FCL. The operating principles that govern an application of saturated core as a FCL is presented. Then a prototype FCL was designed, implemented and tested in reduced voltage and current conditions. The results obtained from the test shows excellence performance of the device in both normal and fault conditions. In order to investigate the feasibility of the device, a FCL was designed for a real distribution network using above technique.